Evaluating the implementation performance of a supplier development program. Issue 4 (12th September 2016) - Routroy, Srikanta; Pradhan, Sudeep Kumar; Sunil Kumar, C.V.
Abstract : Purpose: The purpose of this paper is to quantify, evaluate and compare the implementation performance of a supplier development (SD) program using graph theoretic approach (GTA). Design/methodology/approach: Broadly 13 critical success factors (CSFs) were identified and they were classified into four significant categories (SCs). Featuring these SCs and CSFs under each SC, GTA was proposed for evaluating the implementation performance of SD programs. The analysis was further extended to evaluate the performance of a SD program along the timeline to capture the other influences (if any), eventually compare the results with different performance situations and accordingly set the future targets. Findings: In order to demonstrate the utility of the proposed approach it was applied to an Indian manufacturing company. The results obtained shown that there has been a significant growth achieved in the implementation performance of a SD program over a period of three years (i.e. 12 quarters) along the chosen SCs and CSFs under each SC. It was also found that still there was a performance gap and scope for improvement in the SD program of the case company. Practical implications: The proposed approach is aimed at providing a procedure for evaluating the implementation performance of a SD program. This study is an attempt to assist a manufacturer to assess its SD program and accordingly define its course of actions. Originality/value: Although many issues related to SD have been widely recognized and studied, there are no specific studies available in the literature to assess the implementation performance of SD programs along the timeline. The proposed model has the ability to capture the performance and interdependencies of SCs, CSFs under each SC and also to quantify the implementation performance of a SD program along the timeline.